Monitoring of Coral Reef Cover in the waters of Bunaken National Park, Popapreng Village, South Minahasan Regency, North Sulawesi Province - Jeremi O. Kantohe; Saroyo; Eko Wahyu Handoyo; Adelfia Papu (Universitas Sam Ratulangi, 2025)
Coral reefs are one of the coastal ecosystems that have an important role as a place to look for food, shelter, and breeding grounds for other biota. Corals are invertebrates that are included in the phylum Coelenterata (hollow animal) or Cnidaria. Whereas coral reefs are a collection of millions of polyps. Natural phenomena and various anthropogenic activities threaten the health and existence of coral reefs in the waters of Bunaken National Park, Popareng Village. The purpose of this study is to determine the condition of coral reefs in the waters of Bunaken National Park, Popareng Village. CPCe (Coral Points Count with Excel extension) is used to observe or monitor reef ecosystems. The photo that will be taken using the Underwater Photo Transect (UPT) method from 3 observation stations in Popareng’s Waters will be used as this research database. The photos consist of 50 slides for each station. Photos were taken to represent Popareng’s waters. Each photo was processed in the CPCe by using 30 random points. The condition of the coral reefs in Popareng was moderate. The results of coral reef health conditions at three stations in Popareng reveal poor (21.67%) in station 1; good (54.53%) in station 2; and moderate (32.37%) in station 3.